(untitled) (Lex localis - Journal of Local Self-Government, 2025)
This study aimed to explore the possibility of predicting the variable of citizenship through the dimensions of election. To achieve the study’s objective, a citizenship and election scale comprising 22 items was utilised. The study sample consisted of 264 citizens. The results indicated that the level of awareness of the concept of citizenship among the study sample was moderate and that there was a positive correlation between citizenship and voting in elections. The results of the linear regression analysis further revealed that citizenship could be predicted through the dimensions of election